Integrating Local Wisdom into Physics Learning: Developing an Android Application "Perahu Dayung" to teach Physics - Iin Suminar; M Reza Dwi Saputra; Mulinda Dewi Lestari; Nur Endah Susilowati (Jurnal Pendidikan Fisika dan Sains (JPFS), 2025)
This study developed an Android-based physics learning media integrating local wisdom—Perahu Dayung (Rowing Boat)—to improve student engagement and contextual understanding of Newtonian mechanics. Using a Research and Development (R&D) approach with the Four-D model (Define, Design, Develop, Disseminate), the study began with classroom observations, interviews, and literature review to identify learning needs. The media was designed with a storyboard and prototype, then developed using Unity 3D. Expert validation involved physics lecturers, teachers, and peer reviewers. Trials included 10 students (limited) and 20 tenth-grade students (field trial) at Ferdy Ferry Putra Senior High School, Jambi, using a one-group pretest-posttest design. Instruments included tests and evaluation sheets. The resulting app, Fisika Asik, features interactive quizzes, animations, and cultural content. Validation scores were high for content (4.6) and media (4.4). Learning outcomes showed moderate improvement with a normalized gain of 0.38. The results indicate the media is effective, engaging, and culturally relevant. Integrating local culture offers a contextualized learning approach. Further studies are recommended to expand testing and enhance features.